Ultra‐High Temperature Treatment and Storage of Infant Formula Induces Dietary Protein Modifications, Gut Dysfunction, and Inflammation in Preterm Pigs. Issue 20 (12th September 2022) - Sun, Jing; Akıllıoğlu, Halise Gül; Aasmul‐Olsen, Karoline; Ye, Yuhui; Lund, Pernille; Zhao, Xiao; Brunse, Anders; Nielsen, Christian Fiil; Chatterton, Dereck E. W.; Sangild, Per Torp; Lund, Marianne N.; Bering, Stine Brandt
Abstract : Scope: Ready‐to‐feed liquid infant formula is increasingly used for preterm infants when human milk is unavailable. These formulas are sterilized by ultra‐high temperature treatment, but heating and storage may reduce bioactivity and increase formation of Maillard reaction products with potential negative consequences for immature newborns. Methods and results: Using preterm pigs as a model for sensitive newborn infants, the study tests the intestinal responses of feeding experimental liquid formula within 5 days. A pasteurized formula (PAST) with the same nutrient composition but less protein modifications serves as control to ultra‐high temperature‐treated formula without (UHT) and with prolonged storage (SUHT). Relative to PAST, UHT contains lower levels of lactoferrin and IgG. Additional storage (40 °C, 60 days, SUHT) reduces antimicrobial capacity and increases non‐reducible protein aggregates and Maillard reaction products (up to 13‐fold). Pigs fed SUHT have more diarrhea and show signs of intestinal inflammation (necrotizing enterocolitis) compared with pigs fed PAST and UHT. These clinical effects are accompanied by accumulation of Maillard reaction products, protein cross‐links, and inflammatory responses in the gut. Conclusion: The results demonstrate that feeding UHT infant formulas, particularly after prolonged storage, adversely affects gut maturation and function in preterm pigs used as a model of preterm infants. Abstract : Ready‐to‐feed infant formulas are often used for preterm infants when human milk is unavailable. These formulas are treated with ultra‐high temperature, but during storage, protein modifications are induced. The study shows that stored formulas adversely affect gut maturation and function in preterm pigs. The clinical consequences of feeding infant formulas with a high degree of protein modifications for preterm infants are unknown.